THE PROFICIENCY OF THE THIRD-SEMESTER STUDENTS OF THE ENGLISH STUDY PROGRAM UNIVERSITAS RIAU IN COMPREHENDING READING SECTION OF TOEFL - Melda Dwi Vega; Eliwarti; Novitri (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This descriptive quantitative research aims to examine the reading proficiency of third-semester students in the English study program at FKIP Universitas Riau, specifically in the Reading Section of the TOEFL test. The research population comprised 119 students, and the total sampling technique was used. The instrument was a TOEFL Reading Comprehension test consisting of 50 multiple-choice questions. Students’ scores were analyzed according to the test blueprint in alignment with the Reading Comprehension III syllabus. The results indicate that the average score was 37, categorizing students’ reading proficiency at a poor level. Among the reading skills, using context clues for vocabulary achieved the highest score (58), while scanning for details recorded the lowest score (43). These findings suggest that third-semester students at FKIP Universitas Riau need to enhance their reading comprehension skills in the TOEFL Reading Section to achieve higher scores.